2012
DOI: 10.1074/jbc.m111.294157
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Autophagy by Palmitic Acid via Protein Kinase C-mediated Signaling Pathway Independent of mTOR (Mammalian Target of Rapamycin)

Abstract: Background: Palmitic acid is a saturated fatty acid known to cause lipotoxicity in cells. Results: Palmitic acid induces autophagy, which is independent of mTOR regulation. Conclusion: Palmitic acid-mediated autophagy is regulated via PKC-␣ and acts as a cell survival mechanism. Significance: Our data reveal a novel mechanism underlying free fatty acid-mediated autophagy and suggest the importance of autophagy in bioactivity of fatty acids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
81
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(87 citation statements)
references
References 51 publications
5
81
1
Order By: Relevance
“…The role of DAG in this process is likely linked to its function as a lipid second messenger. DAG activates a signaling cascade involving protein kinase C, with subsequent activation of the class III phosphatidylinositol 3-kinase, Vps34, which is involved in autophagosome formation and maturation (Eisenberg-Lerner and Kimchi, 2012; Shibasaki et al, 2009; Tan et al, 2012). We hypothesized that lipin-1–generated DAG is important in autolysosome formation, and that lack of lipin-1 impairs PKC and Vps34 activation.…”
Section: Resultsmentioning
confidence: 99%
“…The role of DAG in this process is likely linked to its function as a lipid second messenger. DAG activates a signaling cascade involving protein kinase C, with subsequent activation of the class III phosphatidylinositol 3-kinase, Vps34, which is involved in autophagosome formation and maturation (Eisenberg-Lerner and Kimchi, 2012; Shibasaki et al, 2009; Tan et al, 2012). We hypothesized that lipin-1–generated DAG is important in autolysosome formation, and that lack of lipin-1 impairs PKC and Vps34 activation.…”
Section: Resultsmentioning
confidence: 99%
“…Knock down of phosphatase and tensin homologue deleted on chromosome 10 (PTEN), a potent regulator of autophagy, reduced PMA‐induced NETosis in HL‐60 cells and overexpression increased it 76. PKC has been shown to stimulate autophagy which in response to certain stimuli can be independent of mTOR, offering a potential explanation for this discrepancy 77. Figure 2 demonstrates how different stimuli resulting in NETosis can have differential effects on autophagy.…”
Section: Histone Processing and Active Release During Netosismentioning
confidence: 99%
“…Moreover, a cell model demonstrated a pro-survival role of autophagy in the pathogenesis of NAFLD. Tan et al [25] found that restoring autophagy function prevents hepatocyte apoptosis upon palmitate lipotoxicity. Our study showed that autophagy was initiated after 4 weeks of HFD consumption, but not after 16 weeks of HFD consumption, whereas apoptosis was activated after receiving the HFD for 8 weeks.…”
Section: Figmentioning
confidence: 99%